Impact of glycemic control on brain microstructure in type 2 diabetes mellitus: insights from diffusion tensor imaging - Guanye Zhang; Huanhua Wu; Qian Cao; Jiabin Mo; Xiaozheng Cao; Hong Luo; Xiangyu Tan; Hongru Ou (BMC Medical Imaging)
Abstract Background Type 2 diabetes mellitus (T2DM) has been associated with brain microstructural alterations, potentially contributing to cognitive decline and neurodegeneration. Diffusion tensor imaging (DTI) provides a non-invasive method to assess these changes. However, the relationship between glycemic control and brain microstructural integrity remains unclear. This study aims to investigate the association between glycemic control and brain microstructural changes in T2DM using DTI. Methods This retrospective study included 90 participants (30 healthy controls, 60 T2DM patients) who underwent 1.5T MRI DTI at The Affiliated Shunde Hospital of Jinan University between January 2023 and May 2024. T2DM patients were categorized into well-controlled (HbA1c < 7%, n = 30) and poorly controlled (HbA1c ≥ 7%, n = 30) groups. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values were analyzed across multiple white matter regions. Pearson’s correlation was used to assess associations between HbA1c and DTI metrics, while group differences were evaluated using Bayesian effect size estimation. Results HbA1c negatively correlated with ADC values in the right hippocampus (r = -0.33, p = 0.0013), suggesting a relationship between poor glycemic control and increased tissue diffusivity. A weak but significant positive correlation between HbA1c and FA in the right hippocampus (r = 0.23, p = 0.03) was observed. ADC values were higher in the poorly controlled T2DM group, indicating potential diabetes-related microstructural changes. No significant FA or ADC differences were found in other brain regions (p > 0.05). Conclusions Poor glycemic control in T2DM is associated with microstructural alterations in the right hippocampus, potentially reflecting early neurodegenerative processes. Longitudinal studies are needed to further investigate these findings.